Cerebral Sinus Venous Thrombosis in Systemic Lupus Erythematosus - Asep Riswandi; Pinto Desti Ramadhoni; Nova Kurniati; Raden Muhammad Faisal (AKSONA, 2022)
Introduction: Cerebral sinus venous thrombosis (CSVT) is a major cause of stroke in young patients. The incidence of CSVT ranging from 1-12 cases per 1 million adults per year. Autoimmune diseases such as Systemic Lupus Erythematosus (SLE) can cause CSVT. The incidence of CSVT involvement in SLE is 1%. It is characterized by thrombosis in the sinuses and veins, which causes various symptoms, such as headache, seizures, motor weakness, and decreased consciousness. Cases: We report a case of a 20-year-old woman with SLE who complained of seizures accompanied by weakness on both sides of the body and a history of headaches. There is an increase in D-dimer, with positive ANA and anti-ds-DNA tests. A non-contrast CT scan of the head showed a lobar venous infarct with hyperdense lesions, a head non-contrast MRI/MRV revealed a dural sinus thrombosis with a deep cortical/subcortical venous infarct, no bleeding was seen. Patients were given Fondaparinux sodium therapy for 5 days, followed by Warfarin sodium for 3-12 months with a target INR   of 2.0-3.0, and control SLE by administering immunosuppressants gave better outcomes for patients. Conclusion: The diagnosis of CSVT in this patient was based on clinical suspicion and imaging confirmation, and elevation of D-dimer. Non-contrast CT of the head as an initial examination often shows normal imaging. Still, there is also an image of a hyperdense lesion that usually causes an incorrect diagnosis, resulting in delays in therapy. Anticoagulation in CSVT should still be given even if there is bleeding.